Impact of combining acerola by-product with a probiotic strain on a gut microbiome model - Bianchi, Fernanda [UNESP]; Lopes, Natalia Pontin [UNESP]; Adorno, Maria Angela Tallarico; Sakamoto, Isabel Kimiko; Genovese, Maria Inés; Saad, Susana Marta Isay; Sivieri, Katia [UNESP] (Taylor & Francis, 2018)
In this study, we first investigated the survival of three probiotic strains, individually and combined with acerola by-product during simulated gastrointestinal conditions. Next, we investigated the effects of acerola by-product combined with Bifidobacterium longum BB-46 on a gut microbiota model (SHIME®). Chemical composition, total phenolic compounds, antioxidant activity of the acerola by-product and microbial counts, denaturing gradient gel electrophoresis (DGGE), ammonium ions (NH+ 4) and short-chain fatty acids (SCFAs) analysis of the SHIME® samples were performed. Acerola by-product revealed high protein and fibre, reduced lipid contents, and showed to be an excellent source of total phenolic compounds with high in vitro antioxidant activity. A decreased amount of NH+ 4 in the ascending colon and an increase (p <.05) in SCFAs were observed in the three regions of colon during treatment with BB-46 and acerola by-product. BB-46 combined with acerola by-product showed positive effects on the gut microbiota metabolism in SHIME® model.
Keywords: acerola by-product; human gut microbiota; phenolic compounds; Probiotic; SHIME®